Deciphering the nature and statistical optimization of antimicrobial metabolites of two endophytic bacilli - Raghda S. Isleem; Ahmed M. Eid; Saad El-Din Hassan; Khaled M. Aboshanab; Ghadir S. El-Housseiny (AMB Express)
Abstract In this study, Allium sativum, garlic, was selected to isolate endophytic bacteria and to evaluate the antimicrobial, antiviral, antioxidant, and cytotoxic activities of their produced metabolites followed by identification of the biosynthetic gene cluster of the antimicrobial metabolites using Oxford Nanopore Technology (ONT). Two bacterial isolates, C6 and C11, were found to have a broad-spectrum antagonistic effect against four standard microbial strains and were molecularly identified using 16 S ribosomal RNA sequence analysis and deposited in a local culture collection as B. velezensis CCASU-C6, and B. subtilis CCASU-C11, respectively. Optimization for the maximum production of antimicrobial metabolites revealed that a four-day incubation period was optimal, with sucrose and tryptone serving as the best carbon and nitrogen sources for the fermentation media. Response surface methodology model using the central composite design was created resulting in a 1.2-fold and 1.8-fold improvement in antimicrobial metabolite(s) production of C6 and C11 isolates, respectively. The optimal production conditions were found to be a temperature of 33 °C, pH of 7, and an agitation rate of 200 rpm for C6 metabolite, and a temperature of 37 °C, pH of 7, and an agitation rate of 250 rpm for C11 metabolite. Both bacterial isolates displayed antioxidant and antiviral activity and mild cytotoxic action. Genomic sequence and antiSMASH analysis showed that the biosynthetic gene clusters of bacillomycin, mycosubtilin, fengycin, and macrolactin H in B. velezensis CCASU-C6 and bacillibactin and Macrolactin H in B. subtilis CCASU-C11 showed 100% conservation.